Комплексный критерий оценки экономической эффективности систем очистки судовых нефтесодержащих вод - Хлебникова, В.В. (Культура народов Причерноморья, 2014)
В статье получена новая формула для определения коэффициента экономической эффективности систем очистки судовых нефтесодержащих вод, который является комплексным и интегрированным критерием для оценки оптимальности основных технико-экономических показателей и системы в целом, а также позволяет усовершенствовать методы расчета экономической эффективности системы. У статті отримана нова формула для визначення коефіцієнта економічної ефективності систем очищення суднових нафтовмісних вод, який є комплексним і інтегрованим критерієм для оцінки оптимальності основних техніко-економічних показників і системи в цілому, а також дозволяє удосконалити методи розрахунку економічної ефективності системи. In the article the necessity of comprehensive estimation of the cleaning systems of oil-contain waters of the ship is exposed and a new formula for determination of coefficient of economic efficiency of the cleaning systems of oil-contain waters of the ship is got, that is a complex and integrated criterion for the estimation of optimality of basic technical and economic parameters and system on the whole. This criterion allows to perfect the method of calculation of economic efficiency of the cleaning systems of oil-contain waters of the ship and minimize expenses on water treatment, in connection with that on the real moment such criterion absents for the cleaning systems of oil-contain waters of the ship. Also in the article analytical equalization of dependence of cost of the cleaning systems of oil-contain waters of the ship from its productivity is certain and dependence of cost o of the cleaning systems of oil-contain waters of the ship on its cleansing ability is built and its rational optimum is certain. Rational cleansing ability of the cleaning systems of oil-contain waters of the ship is certain. All of it allows complex and comprehensively to estimate efficiency of work of the system.